Tissue‐specific expression of ribosomal protein paralogue eRpL22‐like in Drosophila melanogaster eye development. Issue 9 (31st July 2020) - Gershman, Brett W.; Pritchard, Caroline E.; Chaney, Kenneth P.; Ware, Vassie C.
Abstract: Background: Differences in core or tissue‐specific ribosomal protein (Rp) composition within ribosomes contribute to ribosome heterogeneity and functional variability. Yet, the degree to which ribosome heterogeneity modulates development is unknown. The Drosophila melanogaster eRpL22 family contains structurally diverse paralogues, eRpL22 and eRpL22‐like. Unlike ubiquitously expressed eRpL22, eRpL22‐like expression is tissue‐specific, notably within the male germline and the eye. We investigated expression within the developing eye to uncover tissue/cell types where specific paralogue roles might be defined. Results: Immunohistochemistry analysis confirms ubiquitous eRpL22 expression throughout eye development. In larvae, eRpL22‐like is ubiquitously expressed, but highly enriched in the peripodial epithelium (PE). In early pupae, eRpL22‐like is broadly distributed in multiple cell types, but later, is primarily enriched in interommatidial hair cells (IoHC). Adult patterns include the ring of accessory cells around ommatidia. Adult retinae IoHC patterning phenotypes (shown by scanning electron microscopy) may be linked to RNAi‐mediated eRpL22‐like depletion within larval PE. Immunoblots and polysome profile analyses show multiple variants of eRpL22‐like across development, with the variant at the expected molecular mass co‐sedimenting with active ribosomes. Conclusion: Our data reveal differential patterns of eRpL22‐like expression relative to eRpL22 and suggest a specific role for eRpL22‐like in developmental patterning of the eye. Key Findings: Ribosomal protein paralogues eRpL22 and eRpL22‐like are co‐expressed in the developing eye. eRpL22‐like expression patterns change depending on developmental stage. eRpL22‐like is enriched in the larval peripodial epithelium (PE), the pupal interommatidial hair cell (IoHC), and the ring of accessory cells in adult ommatidia. IoHC orientation and structural phenotypes in adult retinae may be associated with RNAi‐mediated depletion of eRpL22‐like within the PE of third instar larvae, suggesting a role for eRpL22‐like in IoHC patterning. Different molecular variants of eRpL22‐like are expressed at different development stages, but not all variants associate with ribosomal components.